A Review of Conceptual Frameworks in Educational Research - Saraswata Das (AG Volumes, 2025)
By explaining their relationships and the circumstances influencing a research environment and the investigation of the phenomena inside it, a conceptual framework unifies all the components of a study. This review examines the concept of conceptual frameworks within educational research, focusing on the meaning and classification of educational research and the importance of conceptual frameworks. Educational research is highlighted as a scientific, applied, interdisciplinary, and multidisciplinary process employing quantitative and qualitative approaches. The review identifies shared challenges among trainers and trainees in research methodology and emphasizes experiential, strength-based, and critically democratic learning. A well-constructed conceptual framework, grounded in comprehensive literature, is essential for clarifying relationships and guiding the research process.